1999
DOI: 10.1006/dbio.1999.9217
|View full text |Cite
|
Sign up to set email alerts
|

Dynein–Dynactin Function and Sensory Axon Growth duringDrosophilaMetamorphosis: A Role for Retrograde Motors

Abstract: Mutations in the genes for components of the dynein-dynactin complex disrupt axon path finding and synaptogenesis during metamorphosis in the Drosophila central nervous system. In order to better understand the functions of this retrograde motor in nervous system assembly, we analyzed the path finding and arborization of sensory axons during metamorphosis in wild-type and mutant backgrounds. In wild-type specimens the sensory axons first reach the CNS 6-12 h after puparium formation and elaborate their termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Dynein and dynactin are the major components of the retrograde motor system of axonal transport and also mediate the anterograde transport of short axonal microtubules (Ahmad et al, 1998(Ahmad et al, , 2006. In Drosophila mutants of dynactin, the terminal branching of sensory neurons is greatly impaired (Murphey et al, 1999), perhaps reflecting the role of dynein and dynactin in the transport of microtubule fragments into branches.…”
Section: Mechanisms Of Collateral Branch Maturation: Targeting Of Micmentioning
confidence: 99%
“…Dynein and dynactin are the major components of the retrograde motor system of axonal transport and also mediate the anterograde transport of short axonal microtubules (Ahmad et al, 1998(Ahmad et al, , 2006. In Drosophila mutants of dynactin, the terminal branching of sensory neurons is greatly impaired (Murphey et al, 1999), perhaps reflecting the role of dynein and dynactin in the transport of microtubule fragments into branches.…”
Section: Mechanisms Of Collateral Branch Maturation: Targeting Of Micmentioning
confidence: 99%
“…Interestingly, the sensory axons in ctp homozygous adults failed to form proper branches and seemed to grow in altered trajectories. Similar phenotype occurred when a dominant negative Glued gene product was expressed in these neurons (Murphey et al, 1999). All these suggest that DDLC1 could also regulate spectrin-Dynactin-Dynein interaction at the growth cones, and this would maintain cell growth.…”
Section: Role Of Spectrin In Cell Growth At the Distal Endmentioning
confidence: 58%
“…It is required to maintain the retrograde IFT (Pazour et al, 1998), and the assembly of Dynein arms and radial spoke structures of the axoneme (Yang et al, 2001). Studies in Aspergillus have shown that the NUDG/ LC8 is required to maintain nuclear migration, cell growth, and distal end localization of Dynein at higher temperature (Beckwith et al, 1998;Liu et al, 2003), and studies in Drosophila suggested that both DLC1 (ctp) and P150 Dynactin (Glued) are involved in maintaining axonal growth in sensory neurons (Phillis et al, 1996;Murphey et al, 1999). Together, these data suggest that DLC1/LC8 is required for cell growth in a variety of different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Axonal projections from lch5 have been mapped and also show some diversity (Merritt and Whitington, 1995, Smith and Shepherd, 1996, Merritt, 1997, Schrader and Merritt, 2000. In the fCHO, several Gal4 lines (see Brand and Perrimon (1993) and Duffy (2002) for explanation of these genetic tools) express in different subsets of neurons, with different projection patterns into the thoracic ganglia (Phillis et al, 1996, Reddy et al, 1997, Murphey et al, 1999. It is not known whether any of these also express in JO.…”
Section: B Amentioning
confidence: 99%